2021
DOI: 10.3171/2020.8.spine201232
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous translation on two rods improves the correction and apex translocation in adolescent patients with hypokyphotic scoliosis

Abstract: OBJECTIVEThe objectives of this study were to apply the simultaneous translation on two rods (ST2R) maneuver involving rods contoured with a convexity at the desired thoracic kyphosis (TK) apex level and to assess the effects on the ability to support triplanar deformity corrections, including TK apex improvement, in patients with hypokyphotic adolescent idiopathic scoliosis (AIS).METHODSUsing retrospective analysis, the authors examined the digital records that included 2- to 4-week, 1-year, and 2-year postop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Accordingly, the technique of simultaneous translation was superior in restoring thoracic kyphosis. Few other studies reported similar results (22,23).…”
Section: Discussionmentioning
confidence: 54%
“…Accordingly, the technique of simultaneous translation was superior in restoring thoracic kyphosis. Few other studies reported similar results (22,23).…”
Section: Discussionmentioning
confidence: 54%
“…2,3 Curvature corrections aimed to alleviate disability, reduce neurological risk, and improve patients' self-image generally involve surgical translation and rotation techniques followed by spinal fixation. [4][5][6][7] Contemporary correction maneuvers employ instrumentation comprising pedicle screws (PS) to provide a strong fixational force enabling vertebral manipulation and correction maintenance. PS insertion requires meticulous care not to impair adjacent and critical nerve and vasculature structures.…”
Section: Introductionmentioning
confidence: 99%